Experimental test results study future of physical profile of the aviation. - Orlenko N. A. (Kharkov National Pedagogical University, 2012)
He results of studies of the effectiveness of the proposed work program for the training of professional-applied physical training future pilots. Based on the analysis of the data determined by the level of physical fitness, and also revealed the dynamics of the motor characteristics of future pilots. The got results were compared in the control group of students of 1-2 courses of speciality "Aeronavigation" (40 men) and to the experimental group of 1-2 of speciality "Exploitation of aircrafts" (40 men). The norms of certifying were analysed for competition physical preparation during all period of education. Conducted experiment gave an opportunity to define the level of general physical preparedness of future pilots. It is proved that in the future pilots of physical fitness are a wide range of knowledge in physical education and professional-applied physical training, which makes the learning process more effective.